2010
DOI: 10.1103/physrevb.82.045309
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbate-induced roughening of Si(100) by interactions at steps

Abstract: Through a detailed study of Cl adsorption on Si͑100͒ using scanning-tunneling microscopy, we identified sites at steps where adsorption leads to roughening and the formation of extended pits and regrowth structures. Using the equilibrium occupation probabilities obtained from experiment, we were able to identify firstnearest-neighbor interactions that destabilized the surface and, when included in Monte Carlo simulations, reproduced the observed pit and regrowth structures. These findings force a reevaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…3(c). Upon hydrogen chemisorption, the nonrebonded SB step edge becomes energetically favorable and dominates the monolayer SB step structures on hydrogenterminated Si(100) surfaces [73][74][75]. We did not observe band gap edge states or local charging effects across either SA or SB step edges on hydrogen-terminated Si(100) surfaces, and the STS spectra across both the SA and SB step edges are essentially the same as the brown curve shown in Fig.…”
Section: Tunneling Spectra At the Single-layer Sb Step Edgementioning
confidence: 55%
“…3(c). Upon hydrogen chemisorption, the nonrebonded SB step edge becomes energetically favorable and dominates the monolayer SB step structures on hydrogenterminated Si(100) surfaces [73][74][75]. We did not observe band gap edge states or local charging effects across either SA or SB step edges on hydrogen-terminated Si(100) surfaces, and the STS spectra across both the SA and SB step edges are essentially the same as the brown curve shown in Fig.…”
Section: Tunneling Spectra At the Single-layer Sb Step Edgementioning
confidence: 55%
“…Filled circles correspond to the preferential step adsorption interaction (PSAI) model. The dependence of pit area on coverage is clearly different than those of previous models Experimentally this is not observed [7] and theoretically it was found that two Cl atoms adsorbed at a dimer close to a vacancy are just as energetically stable as they would be in an undamaged region of the surface [19]. One is then inclined to consider that adsorbate clustering does not affect the substrate energetics and that it is a consequence of an effective attractive interaction between adjacent doubly occupied dimer.…”
Section: Resultsmentioning
confidence: 77%
“…Recently, a different adsorbate-substrate interaction in the Cl/Si(100) system has been reported that can be responsible for stabilizing steps and then for surface roughening [7]. It was reported that Cl tends to adsorb at rebonded S B step edged sites and the energy difference respect to sites at the terrace was calculated to be *0.14 eV.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a direct comparison of the amounts of incorporated Al atoms to ejected Si atoms after AlCl 3 exposure is complicated by the presence of Cl on the surface, which is known to roughen and etch Si(100), producing both adsorbed Si islands and Si vacancies. [46][47][48][49][50] Therefore, we characterized the amount of incorporated Al with SIMS depth profiling.…”
Section: Al Incorporationmentioning
confidence: 99%